Production of plastic from marine algae - Paveswari, Sithambaranathan (2011)
The two objectives of this research are to produce plastic that is environmental friendly whereby the plastic produced can be at least slightly decomposed to smaller substances by the living organisms from marine algae and also to characterize the plastic that have been produced from the marine algae via mechanical and physical testing. In this study, algae which are Red Eucheuma cottonii are the raw material whereby Low Density Poly Ethylene (LDPE) is the additional plasticizer which aids in the plastic production. Chemical pretreatment was carried out on samples. The samples were then extruded by using twin screw extruder at temperature of 150 ºC and 50 RPM. The extruded samples are then inject molded and characterize by using Fourier Transform Infrared Spectroscopy (FTIR), melt flow index (MFI), tensile testing and density test. From the results obtained, it was found out that this species of algae is not suitable to be the raw material due to the weak properties of intermediate product which is the product after the extrusion process. During the experiments, those algae were difficult to extrude due to easier moisture absorbance from the environment that lead to failure in injection molding during the sample preparation. Hence it can be concluded that the formulation using this species are not suitable for injection molding purpose.